Comparative Study of Indentation Size Effects in As-Sintered Alumina and Alumina Shock Deformed at 6.5 and 12 GPa. (5th December 2012) - Chakraborty, Riya; Mukhopadhyay, Anoop K.; Joshi, Keshaw D.; Rav, Amit; Mandal, Ashok K.; Bysakh, Sandip; Biswas, Sampad K.; Gupta, Satish C.
Abstract : Nanohardness of alumina ceramics determines its performance in all contact-related applications because the issue of structural integrity gets determined at the nanoscale of contact. In spite of the wealth of the literature, however, it is not yet known in significant details how the high-strain rate flyer-plate impact at different pressure affects the nanohardness of dense, coarse grain alumina ceramics. Thus, the load controlled nanoindentation experiments were performed with a Berkovich indenter on an as-received coarse grain ( 10 μ m), high density ( 3.98 gm·cc −1 ) alumina, and shock recovered tiny fragments of the same alumina obtained from gas gun experiments conducted at 6.5 GPa and 12 GPa shock pressures with stainless steel flyer plates. The nanohardness of the as-received alumina was much higher than that of the 6.5 GPa and 12 GPa shock-recovered alumina. The indentation size effect (ISE) was the strongest in alumina shocked at 12 GPa and strong in alumina shocked at 6.5 GPa, but it was mild in the as-received alumina sample. These results were rationalized by analysis of the experimental load depth data and evidences obtained from field emission scanning electron microscopy. In addition, a rational picture of the nanoindentation responses of the as-received and shocked alumina ceramics was provided by a qualitative model.